Eddy Currents Variablity from Satellite Altimetry and Its Relation to Physical Conditions of Java Sea - Kautsar Fadlih Akbar; Ahmad Bayhaqi; Khikmah Muliati; Denny Darmawan (Widyariset, 2020)
Current pattern in Java Sea highly depends on monsoonal cycles, which create alternating conditions according to the seasons throughout the year and potential impacts on eddy currents variability. Using the surface geostrophic current data from satellite altimetry during 2013-2017, this study aims to understand the variability of eddy currents and its relations to the physical condition of the Java Sea such as sea surface temperature (SST), sea surface height (SSH), and chlorophyll-a concentration (CHL). Results showed 60 occurrence of eddy currents in the study area, 40 cyclonic and 20 anticyclonic. The largest cyclonic eddy observed in April 2013 (112.05, -5.37) with a diameter of 134.07 km, while the largest anticyclonic eddy observed in October 2017 (114.54, -6.24) with a diameter of 159.69 km. Cyclonic eddy has lower SSH and cold core while anticyclonic eddy has higher SSH and warm core. Despite having an unclear pattern during the five years period, the occurence of Eddy current has a potentially indirect influence on Chl-a concentration.